Podocytes are the major source of IL-1α and IL-1β in human glomerulonephritides - Niemir, Zofia; Stein, Henning; Dworacki, Grzegorz; Mundel, Peter; Köhl-Hackert, Nadja; Fröhlich, Boris Erwin; Autschbach, Frank; Andrassy, Konrad; Ritz, Eberhard; Waldherr, Rüdiger; Otto, Herwart F. (Kidney international, 1997)
Podocytes are the major source of IL-1α and IL-1β in human glomerulonephritides. To address the question of in situ production of IL-1α and IL-1β in proliferative and non-proliferative forms of human glomerulo-nephritis (GN), we performed immunocytochemical and in situ hybridization studies on renal biopsies from patients with mesangial IgA-GN (N = 38), idiopathic membranous GN (MGN; N = 12), minimal change disease (MCD; N = 9), focal segmental glomerulosclerosis (FSGS; N = 5) and acute endocapillary GN (AGN; N = 3). Normal kidneys (N = 10) served as controls. Concomitantly, the expression of IL-1 receptor type I (IL-1 RI), IL-1 receptor type II (IL-1 RII) and of IL-1 receptor antagonist (IL-1 RA) was analyzed. Antibodies against antigens expressed on podocytes (PP-44), endothelial cells (CD31) and monocytes/macrophages (CD11b, CD14, CD68) were applied to attribute the expression of IL-1/IL-1 related peptides to intrinsic glomerular and/or blood-derived infiltrating cells. Our results demonstrate that IL-1 RII is constitutively expressed on endothelial cells, and its expression can be induced in proximal tubular cells and in the interstitium. In diseased glomeruli podocytes are capable of producing IL-1α/β. In MGN and MCD/FSGS, the expression of both IL-1 forms is particularly noted in early stages of the disease and is not only accompanied by a marked reactivity for IL-1 RI, but also for IL-1 RA. In segmental sclerosing lesions in FSGS and in IgA-GN with marked glomerular proliferation and/or sclerosis, a reduced expression of the PP-44 antigen and a diminished ability of podocytes to produce IL-1/IL-1 related peptides are noted. These results suggest that intrinsic glomerular production of IL-1 may be of relevance for the protection of glomeruli from continuing injury.